Effectiveness of Acupressure For Dysmenorhore Patients: A Literature Review - Sri Wahono, Alif; Putri Asad Andiza, Fandiza Rizkina; Tri Subagia, Rillo; Nur Alfiah, Dini (International Journal of Social Research, 2024)
Constipation is the most common problem in the elderly with a prevalence of 3.8%-6.3% in Indonesia. Abdominal massage or abdominal massage is non-invasive that is easy to apply without causing side effects. This study aims to determine the effectiveness of Abdominal Massage (AM) on constipation in the elderly. Literature review research was conducted using PICO searches in several databases such as Google Scholar, Science Direct, and Pubmed. There were 9 journals that met the criteria and showed the results that Abdominal Massage performed 5 times a week for 4 weeks, with a duration of 15 minutes applied with moderate pressure (2 cm depth) and 2 hours after eating with p- value< 0.05 showed a significant effect on decreased constipation symptoms in the form of abdominal pain,  stool frequency, straining during defecation and prevention of constipation in both the elderly and stroke patients. It can be concluded that abdominal massage is effective in reducing constipation symptoms and also preventing constipation.